The Influence of Trust, Usability, and Perceived Ease of Use of Financial Technology on Student Behavior Intention of Economic Faculty, UISU Medan - Safrida; Yusrita (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The problem formulations of study is: How is the influence of Trust, Usability and Perception of Ease Financial Technology Usages on Student Behavior Intention of Economic Faculty, UISU Medan. The purpose of this study is to analyze the influence of Trust, Usability and Perception of Ease Financial Technology Usages on Student Behavior Intention of Economic Faculty, UISU Medan. The population in this study was 332 students of semester 5 (five). The sample in this study were 77 students of semester 5 (five). By using descriptive data analysis techniques and multiple linear regression analysis, then: The Trust Variables partially have a positive influence on Student Behavior Intention of Economic Faculty, UISU Medan. The Usability variable partially has a positive influence on Student Behavior Intention of Economic Faculty, UISU Medan. The Perceived Ease of Use variable partially has an influence on Student Behavior Intention of Economic Faculty, UISU Medan. The variables of Trust, Usability and Perceived Ease of Use simultaneously had a positive influence on Student Behavior Intention of Economic Faculty, UISU Medan. The value of Determination in this study was 0.522. This shows that 52.2% of Behavioral Intentions variables can be explained by the variables of Trust, Usability and Perceived Ease of Use, the remaining 47.8% is influenced by other factors not done in the study.